Cephalomalthinus simplicicornis (Wittmer, 1993) rev. stat. et comb. n.: a resurrected soldier beetle (Coleoptera, Cantharidae) from Taiwan based on morphological and molecular data - Hsiao, Yun; Tsai, Cheng-Lung (Zootaxa, 2019)
The genus Cephalomalthinus Pic, 1921 is a diverse group of soldier beetles known from East Asia, with modifications on the male antennae, which are traditionally used for species delimitation. However, antennae are uniform in some Cephalomalthinus groups, thus making species identification difficult. In this study, both morphological and molecular data are applied to solve the generic classification and species status of Micropodabrus simplicicornis Wittmer, 1993, which was recently synonymized with Cephalomalthinus formosanus (Pic, 1910). We analyzed holotypes, multiple specimens and DNA barcodes to re-examine the validity of this synonymy. The results suggest that M. simplicicornis should be resurrected from the synonymy with C. formosanus, and a new combination, Cephalomalthinus simplicicornis (Wittmer, 1993) rev. stat. et comb. n., is proposed accordingly. The results highlight the value of multisource taxonomy and the discordance between molecular and morphological data.